A Randomized Trial to Compare Topical MJ1 with Routine Care for the Treatment of Cutaneous Leishmaniasis - Mohsen Janghorbani; Masoumeh Faraji; Javad Ramazanpour; Reza Fadaei (Iranian Journal of Health, Safety and Environment, 2015)
The objective of this study was to assess the relative efficacy and tolerability of topical MJ1 compared to routine care in the treatment of histologically proven CL. A total of 150 patients with 297 lesions were randomly allocated to receive either topical MJ1 agent as a paste to applied to the lesions without cover three times a day for 20 days or routine care (intramuscular injection of meglumine antimonate 20 mg/kg/day for 2 weeks or intralesional 0.5-1 cc for a total of four injection with one week interval). The primary end point of this study was the clinical cure of the lesion. Response to treatment was assessed at 1, 2, 3 and 8 weeks after start of therapy. Of the 132 lesions treated with MJ1, the mean size of lesions decreased from 423.9 to 30.4 mm2, 111 (84.1%) were reduced in size and 21 (15.9%) not responded. Correspondingly, in the 165 lesions treated with routine care, the mean size of lesions slightly increased from 295.8 to 330.5 mm2, 82 (49.7%) were reduced in size and 83 (50.3%) not responded. The differences were statistically significant (P<0.001). No sever adverse effect occurred. The findings highlight that topical treatment with MJ1 agent was much more effective than routine care and is safe and well tolerated.